Efficient degradation of dyes in water by two Ag-based coordination polymers containing 1, 3-bis(3, 5-dicarboxylphenoxy)benzene and N-donor linkers. (1st October 2021) - Shi, Chuncheng; Nie, Zhi-Hui; Zhao, Ling; Lu, Lu; Cheng, Fan; Chen, Xuelin; Tan, Guijian; Liu, Qiang-Qiang; Wang, Jun; Chauhan, Ratna; Kumar, Abhinav
Graphical abstract: Two new Ag(I) coordination polymers having polycarboxylate ligand and nitrogen co-ligand synthesized and their photocatalytic performances to photodegrade aromatic dyes assessed. Abstract: Two new Ag(I) based coordination polymers (CPs), with formula [Ag2 (H2 L)(4, 4′-bipy)2 ·2H2 O] (1 ), and [Ag2 (H2 L)(bpz)2 ] (2 ) (H4 L = 1, 3-bis(3, 5-dicarboxylphenoxy)benzene, 4, 4′-bipy = 4, 4′-bipyridine, and bpz = 3, 3′, 5, 5′-tetramethyl-4, 4′-bipyrazole) have been solvothermally synthesized and characterized. The single crystal X-ray structural analysis reveals that CPs 1 and 2 consist of 3D hydrogen-bonded organic framework with rectangle and grid channels, respectively. In addition, the photocatalytic properties of both 1 and 2 have been assessed under UV light against methyl orange (MO), rhodamine B (RB), methyl blue (MB), neutral red (NR), methylene blue (MB) are investigated in aqueous solutions. The results suggested that percentages of photocatalytic degradation toward MB, Rh B and MO in presence of 1 are 90.24%, 93.56% and 45.11%, respectively in 100 min. While in presence of 2 the percentage photodegradation of MB, Rh B and MO are 84.33%, 55.54% and 4.27% in 100 min. The plausible mechanistic pathways through which newly synthesized CPs executed photodegradation of these dyes have been explained with the aid of band gap calculations implementing density of states and partial density of states.